Creating Space Invaders, a 2D Based Game by Using HTML5 and Javascript - Nazar, Muhammad; Nasrullah, Nasrullah; Syafira, Defy (Gameology and Multimedia Expert, 2024)
Games are one of the entertainment media that people choose to relieve boredom or just to fill their free time. Apart from being an entertainment medium, games can also be a learning medium to improve a person's brain development. Action games provide a good opportunity to train children's agility in thinking. Action games are games with the main feature of rapid shooting facilities with lots of action where players must have fast reaction skills to avoid enemy fire or avoid obstacles. Most of the action games "Space Invaders" are still or even the graphics and specifications are still low and there are almost no good graphics. This is because there are no applications for making games yet, but as time goes by, there are now applications that can make games easily, but these applications are still rarely used.